Hispanic technocracy: from fascism to Catholic authoritarianism in Spain, Argentina, and Chile, 1945-1991 - Kressel, Daniel Gunnar (Cambridge Latin American studies, 2025)
"This book explores how the Cold War Latin American right sought to rescue the essence of Europe's fascist ideology after 1945 by reformulating it into novel authoritarian state models. It will interest students and scholars of Latin American history, political science, economics, sociology, and anthropology"-- Provided by publisher